DAMPAK LAMBANG KOMUNIKASI NONVERBAL TERHADAP UKHUWAH ISLAMIAH KELUARGA PENGANTIN DALAM UPACARA ADAT PERNIKAHAN SUKU JAWA DI KABUPATEN LANGKAT - Bito Reja Ninda Sari (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstrak: Issues examined in this study, firstly, how the community’s role in ceremonial marriage ofJava’s district of Langkat, both the process and ceremony, wedding customs of Java’s district of Langkat,third how to use the emblem of nonverbal communication to ukhuwah Islamiyah family of the bride ina traditional ceremony Javanese wedding in Langkat district, fourth, how the impact of nonverbal communicationemblem of the brotherhood Islamiyah family of the bride in the wedding ceremonies in thedistrict langkat Javanese.The purpose of this research first, to analyze the role of the community in the ceremonial marriage ofJava’s district of Langkat, second, to analyze the process and ceremony, wedding customs of Java’s districtof Langkat, third, to analyze the use of the emblem of nonverbal communication custom wedding Javanesedistrict langkat , Fourth to analyze the impact of nonverbal communication emblem of the Islamic Ukhwahfamily wedding in Langkat.